PERFORMANCE ANALYSIS OF STATE ELEMENTARY SCHOOL HEADMASTERS THROUGH TRAINING AND WORK ENVIRONMENT WITH MOTIVATION AS INTERVENING - Wardani, Yuniatin; Awatara, I Gusti Putu Diva (TRIKONOMIKA, 2019)
This study aims to determine the effect of training and work environment on the performance of the heads of public elementary schools in sub-district Banjarsari of Surakarta city with motivation as an intervening variable. Methods of collecting data with questionnaires on a sample of 30 elementary school. Path analysis results conclude that: 1. The direct effect of training on performance of is greater than the indirect effect of training on performance with motivation mediation, meaning that motivation cannot function as an intervening variable. 2. The indirect effect of the work environment on motivation mediation performance is greater than the correlation between the work environment with motivation, motivation correlation with a performance, meaning that motivation cannot function as an intervening variable. 3. The total effect of training on performance is greater than the total effect of the work environment on performance. Test results concluded that to improve performance is most effective through increasing training without going through intervening variables.